Implementación de un sistema de costos por procesos para la producción avícola de la granja aves y huevos Mishel ubicada en la provincia de Cotopaxi, cantón Latacunga, parroquia Eloy Alfaro, para el período 2012 - Umajinga Umajinga, María Luzmila (2015)
The present research is about the Implementation of a Costs by Process System for the Chickens and Eggs Mishel Farm, in which its determined the lack of a accountable system, which let the control and registrer in an empiric way, by the owners, unknowing the economical and finantial situation in which the farm was, because any data was presented at the end of each period. The methodology used the researching development was of type non experimental, which lets to identify the existent problems in the entity so it was aplied techniques and instruments of researching in order to propose solutions the found problems. Acoording to the got results, the Implementation of a Costs by Process System let to determine which exactitude the real expenses in each period and productive process which involves the breedring and explotation of from which was gotten the true information throunght the presentation of Finantial States and explanatory notes which facilitate the owners to take decisions such as: the costs and expencess of the production avording the wasting.